Dietary glycemic index/glycemic load and their relationship with inflammatory markers in women with polycystic ovary syndrome - Alipour, Beitolah; Roohelhami, Elham; Shahrdami, Farzaneh; Rashidkhani, Bahram (Progress in Nutrition, 2019)
Objective: the present study evaluates energy intake, macronutrient composition and dietary glyce- mic index (GI) and glycemic load (GL) in women with polycystic ovary syndrome (PCOS) and age and body mass index (BMI)- matched controls, and relationship between carbohydrate variables with inflammatory markers. Methods: This case_control study was conducted on 90 women aged 18-35 years including 45 women with PCOS and 45 age and BMI-matched healthy controls. Dietary intakes, GI and GL were assessed using three 24-hour recalls. Biochemical profile including high-sensivity C-reactive protein (hs-CRP), interleu- kin-6 (IL-6) and tumor necrosis factor α (TNF-α) as inflammatory markers and also metabolic variables related to insulin resistance were measured. Anthropometric measurements were performed in all subjects. Results: Dietary GI and starch intake were significantly higher in PCOS group compared with age and BMI-matched control group (P < 0.05). Fasting insulin, homeostatic model assessment of insulin resistance (HOMA-IR) and hs-CRP were higher in patients compared with controls (P < 0.05). No significant cor- relation was detected between biochemical variables and macronutrient intakes. Conclusion: Total energy and macronutrient intakes were similar between the groups except for dietary GI and starch intake. However, quality and quantity of carbohydrate consumed was not associated with insulin resistance and inflammatory markers in the PCOS group.